2023
DOI: 10.1093/braincomms/fcad265
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the anatomy of the gyral white matter: ubi sumus? quo vadimus?

Guillaume Dannhoff,
Phanindra P Poudel,
Chacchu Bhattarai
et al.

Abstract: A cerebral gyrus is made up of an external layer of folded cortex and an inner core of white matter. The architecture of the core has specific features that make it distinct from the white matter of the deep brain regions. Limited externally by the gray matter that covers the top of the gyrus and the neighboring sulci, this gyral white matter is made up of a mix of fiber populations with multiple directions and destinations. The presence of densely packed fibers with multiple crossings, the proximity to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…In order to compare the structural connectivity around the left pOTS proper and gaps in children with a continuous vs. an interrupted sulcus, we performed whole-brain probabilistic tractography from a superficial white-matter layer located under the left pOTS and gap cortex (see Figure 4c for a seed region in an example participant). Mean structural connectivity from these seeds from all children showed strong local connectivity to fusiform and inferior temporal gyri adjacent to the superficial white-matter seeds above the left pOTS, and extending to the middle temporal gyrus, parahippocampal cortex, and anterior OTS (Figure 4c middle panel), consistent with the presence of short, neighborhood association fibers traveling under the sulcal cortex (Dannhoff et al, 2023;Reveley et al, 2015). When comparing structural connectivity between children with interrupted and continuous left pOTS through permutation testing, children with sulcal interruption showed higher local connectivity, as indexed by density maps reflecting the number of reconstructed streamlines, in a cluster located around the posterior section of the left pOTS, after controlling for demographic variables (age, gender and handedness, p<0.01 threshold-free cluster enhancement -TFCE-uncorrected, Figure 4c bottom panel, leftmost map), suggesting a higher development of short-distance connections, in agreement with hypothesis (ii).…”
Section: Why Are Interruptions Beneficial? Left Pots Interruption And...mentioning
confidence: 72%
See 2 more Smart Citations
“…In order to compare the structural connectivity around the left pOTS proper and gaps in children with a continuous vs. an interrupted sulcus, we performed whole-brain probabilistic tractography from a superficial white-matter layer located under the left pOTS and gap cortex (see Figure 4c for a seed region in an example participant). Mean structural connectivity from these seeds from all children showed strong local connectivity to fusiform and inferior temporal gyri adjacent to the superficial white-matter seeds above the left pOTS, and extending to the middle temporal gyrus, parahippocampal cortex, and anterior OTS (Figure 4c middle panel), consistent with the presence of short, neighborhood association fibers traveling under the sulcal cortex (Dannhoff et al, 2023;Reveley et al, 2015). When comparing structural connectivity between children with interrupted and continuous left pOTS through permutation testing, children with sulcal interruption showed higher local connectivity, as indexed by density maps reflecting the number of reconstructed streamlines, in a cluster located around the posterior section of the left pOTS, after controlling for demographic variables (age, gender and handedness, p<0.01 threshold-free cluster enhancement -TFCE-uncorrected, Figure 4c bottom panel, leftmost map), suggesting a higher development of short-distance connections, in agreement with hypothesis (ii).…”
Section: Why Are Interruptions Beneficial? Left Pots Interruption And...mentioning
confidence: 72%
“…For instance, previous work has highlighted that junctions in gyral ridges, known as 3-hinge gyri, serve as hubs in cortico-cortical connections with higher connection degrees, stronger connections, and high betweenness centrality in graphs of structural connectivity (Zhang et al, 2020). The rich connectivity of such regions has also been documented through fine-grained postmortem dissections (Shinohara et al, 2020; as also reviewed in Dannhoff et al, 2023), revealing that 'pyramid shape crossings' are characterized by, and seem to result from, the convergence of both intraand inter-gyral U fibers. Crucially, we showed that such increased local U-shaped fibers also relate to reading skills.…”
Section: Developmental Origins Of the Impact Of Left Pots Interruptio...mentioning
confidence: 98%
See 1 more Smart Citation